Evaluation of structural formation of granular materials using anisotropy of magnetic susceptibility. Issue 5 (4th May 2023) - Ni, Xueqian; Cao, Yupeng; Zhang, Feng; Zhang, Zhao
Abstract: The structure of granular materials is one of the most important influential factors in mechanical behaviors. A few inevitable limitations exist in current optical measuring techniques, such as structure disturbance, operational complexity, and high cost. This study attempts to take a new application of the anisotropy of magnetic susceptibility (AMS) technique to investigate the structure of granular materials. To illustrate the feasibility of the AMS in detecting the structure, each of five different kinds of sand, including beach sand, river sand, aeolian sand, and calcareous sand, was reconstituted by moist tamping method and air pluviation method, respectively. Based on the structural features obtained from the optical and the AMS techniques, the validity and applicability of the AMS technique on granular materials with different magnetic mineral compositions were discussed systematically. It is found that the AMS technique is a feasible and efficient method to investigate the structure of granular materials both in laboratory tests and field sampling tests.